Programming sequential motion steps in 4D-printed hygromorphs by architected mesostructure and differential hygro-responsiveness. (21st July 2021) - Tahouni, Yasaman; Krüger, Friederike; Poppinga, Simon; Wood, Dylan; Pfaff, Matthias; Rühe, Jürgen; Speck, Thomas; Menges, Achim
Abstract: Through their anisotropic cellular mesostructure and differential swelling and shrinking properties, hygroscopic plant structures move in response to changes in the environment without consuming metabolic energy. When the movement is choreographed in sequential time steps, either in individual structures or with a coordinated interplay of various structural elements, complex functionalities such as dispersal and protection of seeds are achieved. Inspired by the multi-phase motion in plant structures, this paper presents a method to physically program the timescale and the sequences of shape-change in 4D-printed hygromorphic structures. Using the FDM 3D-printing method, we have developed multi-layered, multi-material functional bilayers that combine highly hygroscopic active layers (printed with hygroscopic bio-composite materials) with hydrophobic restrictive and blocking layers (printed with PLA and TPC materials). The timescale of motion is programmed through the design of the mesostructured layers and 3D-printing process parameters, including thickness (number of printed active layers), porosity (filling ratio of the active layer), and water permeability (filling ratio of the blocking layer). Through a series of experiments, it is shown that the timescale of motion can be extended by increasing the thickness of the active layer, decreasing the porosity of the active layer, or increasing the filling ratio of the hydrophobic restrictive and blocking layers. Similarly, a lower thickness of the active layer and lower filling ratio of all layers result in a faster motion. As a proof of concept, we demonstrate several prototypes that exhibit sequential motion, including an aperture with overlapping elements where each completes its movement sequentially to avoid collision, and a self-locking mechanism where defined areas of the structure are choreographed to achieve a multi-step self-shaping and locking function. The presented method extends the programmability and the functional capabilities of hygromorphic 4D-printing, allowing for novel applications across fields such as robotics, smart actuators, and adaptive architecture.